Essentials of international relations - Mingst, Karen A. 1947- (Norton, 2004)
[This book provides] coverage of the fundamental topics and basic concepts of international politics. Taking a balanced view of major theoretical approaches - including liberalism and realism, as well as Marxism, feminism, and constructivism - [the author] provides the analytical tools students need to understand world political affairs at the individual, state, and international system levels. [This book] provides expanded coverage of intergovernmental organizations, such as the United Nations, and of nongovernmental organizations, both terrorist and peaceful.